MIKROORGANISME PATOGEN DAN PARASIT DI DALAM AIR LIMBAH DOMESTIK SERTA ALTERNATIF TEKNOLOGI PENGOLAHAN - Said, Nusa Idaman; Marsidi, Ruliasih (Jurnal Air Indonesia, 2005)
Domestic waste are known to be a potential pollutant due to itsÃ¢â‚¬â„¢ organic and inorganic content. It is also harmful for society for its pathogenic microorganism contents such as pathogenic bacteria, viruses, parasitic worms, parasitic protozoa, etc. The lack of domestic waste processing facilities is contributing to the increasing seriousness of this matter.One of the alternative ways to amend the problem is to process the waste individually or semi-communally by utilizing an aerobic-anaerobic biofilter process. Some of the advantage of utilizing this process is: easy maintenance, low operation cost, relatively lower sludge compared to the activated sludgeÃ‚Â  process, can remove nitrogen and phosphorus, relatively lower air supply requirement for aeration, applicable in processing waste water with large amount of BOD and it can also remove suspended solid (SS).Ã‚Â  Results gained from experiments of the Ã¢â‚¬Å“Aerobic-Anaerobic Biofilter CombinationÃ¢â‚¬Â tool prototype, used for processing domestic waste showed that with a hydraulic retention time of 1 to 3 days and a HydraulicÃ‚Â Ã‚Â  re-circulation ratio (HRR) of 1, is a highly efficient process which is: BOD 84.7% - 91%, COD 79.6%-95.3%, SS 94.1% - 95%, Ammonia (NH4-N) 89.3%-89.8%, Detergent (MBAS) 83% - 87% and phosphate (PO4) 44,4% - 47.3%.Ã‚Â Kata kunci : Air limbah domestik, patogen, parasit, biofilter, anaerob, aerob.Ã‚Â